A calcium silicate board powder coating and preparation method thereof

By using low-temperature curing polyester resin and modified degassing agent in powder coating, the adhesion and flatness of powder coating on calcium silicate boards is solved, and the coating effect with high adhesion and flatness is achieved.

CN119081515BActive Publication Date: 2025-04-22FOSHAN JUNMEIQI NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411364100.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2025-04-22
Estimated Expiration
2044-09-28

AI Technical Summary

Technical Problem

The adhesion and flatness of the powder coating on the calcium silicate boards are poor, resulting in uneven coatings and low adhesion.

Method used

The low-temperature cured polyester resin and a modified degassing agent are used. The low-temperature cured polyester resin can be cured at 160°C. The modified degassing agent is grafted by polytetrafluoroethylene wax and unsaturated polyoxyethylene ether to promote the movement of gas from the inside of the coating to the surface, eliminate bubbles, and improve adhesion and flatness.

Benefits of technology

The curing temperature is reduced, the structural stability of the calcium silicate board is maintained, the adhesion between the powder coating and the calcium silicate board is improved, and the flatness of the coating is improved through defoaming, meeting the requirements of high adhesion and flatness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005065714130000091
    Figure BDA0005065714130000091
  • Figure BDA0005065714130000101
    Figure BDA0005065714130000101
Patent Text Reader

Abstract

The present application discloses a calcium silicate board powder coating and a preparation method thereof, belonging to the field of coatings. A calcium silicate board powder coating is prepared from raw materials containing the following weight percentages: 55-70% low-temperature curing polyester resin; 5-8% curing agent; 0.5-1.5% wetting agent; 0.5-1.5% leveling agent; 0.5-1.5% filler; 5-10% flame retardant; 0.6-1% modified degassing agent; balance of pigment and filler; the modified degassing agent is prepared by grafting polytetrafluoroethylene wax with unsaturated polyoxyethylene ether. The present application has the effect of improving the adhesion and flatness of the powder coating on the calcium silicate board.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coatings, and in particular to a calcium silicate board powder coating and a preparation method thereof. Background Art

[0002] Calcium silicate board is a board made of loose short fibers such as inorganic mineral fibers or cellulose fibers as reinforcing materials, and siliceous-calcium materials as the main bonding materials. It is made through pulping, molding, and accelerating the curing reaction in high-temperature and high-pressure saturated steam to form a calcium silicate gel.

[0003] Powder coating is a solid powdered synthetic resin coating composed of solid resin, pigment, filler and additives, which has the advantages of dense coating, good adhesion, impact resistance and toughness. Powder coating has high adhesion to metal surface, so it is generally applied to metal materials.

[0004] Powder coatings are rarely used on calcium silicate boards because bubbles are difficult to eliminate when powder coatings are applied to the surface of calcium silicate boards, which not only causes unevenness in the coating, but also leads to low adhesion between the coating and the calcium silicate board, resulting in poor application effect. Summary of the invention

[0005] In order to improve the adhesion and smoothness of powder coating on calcium silicate board, the present application provides a calcium silicate board powder coating and a preparation method thereof.

[0006] In the first aspect, the calcium silicate board powder coating provided in the present application adopts the following technical solution:

[0007] A calcium silicate board powder coating is prepared from raw materials containing the following weight percentages:

[0008] Low temperature curing polyester resin 55-70%;

[0009] Curing agent 5-8%;

[0010] Wetting agent 0.5-1.5%;

[0011] Leveling agent 0.5~1.5%;

[0012] Filler 0.5-1.5%;

[0013] Flame retardant 5-10%;

[0014] Modified degassing agent 0.6~1%;

[0015] Pigment and filler residue;

[0016] The modified degassing agent is prepared by grafting unsaturated polyoxyethylene ether with polytetrafluoroethylene wax.

[0017] By adopting the above technical solution, when general powder coating is applied to calcium silicate board, due to the high curing temperature, generally 200°C is required, which easily leads to the removal of crystalline water of silicate, affecting the adhesion of powder coating to calcium silicate board and also affecting the flatness of coating. Therefore, low-temperature curing polyester resin is used, which can be cured at 160°C, thereby reducing the curing temperature to maintain the structural stability of calcium silicate board, thereby improving the adhesion of powder coating to calcium silicate board.

[0018] The coating of low-temperature curing polyester resin is prone to residual bubbles, so a modified degassing agent is added. When the above raw materials are melted, the polytetrafluoroethylene wax can migrate to the surface of the coating, and at the same time drive the gas from the inside of the coating to the surface of the coating, and finally leave the coating, thereby playing a degassing role. In addition, after the grafting modification of allyl alcohol polyoxyethylene ether, the compatibility of polytetrafluoroethylene wax and low-temperature curing polyester resin is changed, and the migration of polytetrafluoroethylene wax on the surface of the coating is promoted to be more uniform. In addition, the presence of allyl alcohol polyoxyethylene ether helps to destroy the stability of bubbles, making the bubble film in the coating easier to break. Therefore, it plays a defoaming role while degassing, further reducing the impact of bubbles on the coating, and meeting the requirements of smooth surface and high adhesion of the coating.

[0019] Optionally, the weight ratio of polytetrafluoroethylene wax to unsaturated polyoxyethylene ether used to prepare the modified degassing agent is 1:(0.4-0.5), and the unsaturated polyoxyethylene ether is selected from one or both of allyl alcohol polyoxyethylene ether and isopentanol polyoxyethylene ether.

[0020] By adopting the above technical scheme, the unsaturated double bonds of allyl alcohol polyoxyethylene ether and isopentanol polyoxyethylene ether can be free radical polymerized with polytetrafluoroethylene wax to achieve grafting.

[0021] Optionally, the unsaturated polyoxyethylene ether is a combination of allyl alcohol polyoxyethylene ether and isopentanol polyoxyethylene ether, and the weight ratio of the polytetrafluoroethylene wax, allyl alcohol polyoxyethylene ether and isopentanol polyoxyethylene ether is 1:(0.3-0.35):(0.1-0.15).

[0022] By adopting the above technical solution, allyl alcohol polyoxyethylene ether and isopentanol polyoxyethylene ether are combined to adjust the surface properties of polytetrafluoroethylene wax, thereby improving the ability to destroy bubble films, thereby further improving the defoaming ability of the modified degassing agent.

[0023] Optionally, the polymerization degree of the allyl alcohol polyoxyethylene ether is 20-30, and the polymerization degree of the isopentenol polyoxyethylene ether is 10-15.

[0024] Optionally, the curing agent is triglycidyl isocyanurate.

[0025] Optionally, the wetting agent is an organic silicon-oxygen copolymer, and specifically, the Ruike Chemical wetting agent RK-8209 can be selected.

[0026] Optionally, the leveling agent is polyether-modified polydimethylsiloxane, and specifically BYK-333 may be selected.

[0027] Optionally, the flame retardant is aluminum hydroxide.

[0028] Optionally, the low-temperature curing polyester resin is prepared from neopentyl glycol, cyclohexanedimethanol, terephthalic acid, isophthalic acid, adipic acid, methyl vinyl ether-maleic acid copolymer, trimethylolpropane, a catalyst and a curing accelerator.

[0029] Optionally, the raw materials for preparing the low-temperature curing polyester resin are prepared according to the following weight ratio:

[0030] 35-40 parts of neopentyl glycol;

[0031] 5-10 parts of cyclohexanedimethanol;

[0032] 50-55 parts of terephthalic acid;

[0033] 12-15 parts of isophthalic acid;

[0034] 3-7 parts of adipic acid;

[0035] 2 to 4 parts of methyl vinyl ether-maleic acid copolymer;

[0036] 2-4 parts of trimethylolpropane;

[0037] 0.5-1 part of catalyst;

[0038] 0.2-0.5 parts of curing accelerator.

[0039] By adopting the above technical scheme, the polyester resin prepared from the above raw materials has high curing activity, can be cured at 160°C, and has good fluidity. When the powder coating is cured on the surface of the calcium silicate board, the influence of temperature on the structure of the calcium silicate board can be reduced; the addition of methyl vinyl ether-maleic acid copolymer can improve the flexibility of polyester, improve the impact resistance, and cooperate with the grafted unsaturated polyoxyethylene ether in the modified degassing agent to further improve the adhesion of the coating.

[0040] Optionally, the filler is nano iron powder, and the particle size of the nano iron powder is 50-100 nm.

[0041] By adopting the above technical solution, the nano iron powder has good dispersibility in the low-temperature curing polyester, so the filling effect is good and the density of the coating is improved.

[0042] In the second aspect, the present application provides a method for preparing a calcium silicate board powder coating using the following technical solution:

[0043] A method for preparing a calcium silicate board powder coating comprises the following steps:

[0044] The low-temperature curing polyester resin, curing agent, wetting agent, leveling agent, filler, modified degassing agent and pigment filler are mixed, melted, extruded, cooled, crushed and sieved to obtain the calcium silicate board powder coating.

[0045] Optionally, the preparation method of the modified degassing agent is:

[0046] The polytetrafluoroethylene wax is subjected to low temperature plasma treatment, with a treatment power of 200 to 250 W and a treatment time of 60 to 100 seconds to obtain a pretreated polytetrafluoroethylene wax;

[0047] The pretreated polytetrafluoroethylene wax is stirred and dispersed in water, unsaturated polyoxyethylene ether is added and mixed evenly, and then the initiator solution is added dropwise, and the temperature is gradually raised to 80-85°C while the initiator solution is added dropwise. After the addition is completed, the reaction is continued for 2-3 hours. After the reaction is completed, it is filtered, the filter body is collected and washed to obtain a modified degassing agent.

[0048] By adopting the above technical solution, the polytetrafluoroethylene wax generates free radicals after being treated with plasma. Under the action of the free radicals, the double bonds of the unsaturated polyoxyethylene ether are opened to achieve grafting, thereby improving the surface properties of the polytetrafluoroethylene wax.

[0049] Optionally, the preparation method of the low temperature curing polyester resin is:

[0050] Under the protection of inert gas, neopentyl glycol, cyclohexanedimethanol, terephthalic acid, adipic acid, methyl vinyl ether-maleic acid copolymer, trimethylolpropane and a catalyst are mixed and reacted at 240-250°C for 3.5-4h, water is distilled off during the reaction, and then the temperature is lowered to 225-230°C and isophthalic acid is added to continue the reaction for 3-4h, and then vacuum is drawn to cause polycondensation for 2-3h, the temperature is lowered to 200-210°C, a curing accelerator is added, the reaction is continued for 0.3-0.6h, the temperature is lowered, and the material is discharged to obtain a low-temperature curing polyester resin.

[0051] In summary, this application has the following beneficial effects:

[0052] 1. This application adopts low-temperature curing polyester resin, which can be cured at 160°C, reducing the curing temperature to maintain the structural stability of the calcium silicate board, thereby improving the adhesion between the powder coating and the calcium silicate board; and adding a modified degassing agent, when the above raw materials are melted, the polytetrafluoroethylene wax can migrate to the coating surface, while driving the gas from the inside of the coating to the coating surface, and finally leaving the coating, thereby playing a degassing role. In addition, after the grafting modification of allyl alcohol polyoxyethylene ether, the compatibility of polytetrafluoroethylene wax and low-temperature curing polyester resin is changed, and the migration of polytetrafluoroethylene wax on the coating surface is promoted to be more uniform, and the presence of allyl alcohol polyoxyethylene ether helps to destroy the stability of bubbles, making the bubble film in the coating easier to break, so it plays a defoaming role while degassing, further reducing the impact of bubbles on the coating, and meeting the requirements of smooth coating surface and high adhesion.

[0053] 2. The polyester resin of the present application has high curing activity, can be cured at 160°C, has good fluidity, and reduces the influence of temperature on the structure of the calcium silicate board when it is cured on the surface of the calcium silicate board; the addition of methyl vinyl ether-maleic acid copolymer can improve the flexibility of the polyester, improve the impact resistance, and cooperate with the grafted unsaturated polyoxyethylene ether in the modified degassing agent to further improve the adhesion of the coating. DETAILED DESCRIPTION

[0054] The present application is described in further detail below.

[0055] Preparatory Example 1

[0056] The preparation method of low temperature curing polyester resin comprises the following steps:

[0057] Weigh 3.5 kg of neopentyl glycol, 0.5 kg of cyclohexanedimethanol, 5 kg of terephthalic acid, 0.3 kg of adipic acid, 0.2 kg of methyl vinyl ether-maleic acid copolymer, 0.2 kg of trimethylolpropane, 0.05 kg of catalyst, 1.2 kg of isophthalic acid, and 0.02 kg of curing accelerator.

[0058] The molecular weight of the methyl vinyl ether-maleic acid copolymer is 80,000, the catalyst is specifically monobutyl tin oxide, and the curing accelerator is specifically triphenylethylphosphine bromide.

[0059] Under nitrogen protection, neopentyl glycol, cyclohexanedimethanol, terephthalic acid, adipic acid, methyl vinyl ether-maleic acid copolymer, trimethylolpropane and a catalyst were mixed and reacted at 240°C for 3.5 hours, and water was distilled off during the reaction. The temperature was then lowered to 225°C and isophthalic acid was added to continue the reaction for 4 hours. The mixture was then vacuumed for condensation for 2 hours, the temperature was lowered to 200°C, a curing accelerator was added, the reaction was continued for 0.3 hours, the temperature was lowered to room temperature, and the material was discharged to obtain a low-temperature curing polyester resin.

[0060] Preparatory Example 2

[0061] The preparation method of low temperature curing polyester resin comprises the following steps:

[0062] Weigh 4 kg of neopentyl glycol, 1 kg of cyclohexanedimethanol, 5.5 kg of terephthalic acid, 0.7 kg of adipic acid, 0.4 kg of methyl vinyl ether-maleic acid copolymer, 0.4 kg of trimethylolpropane, 0.1 kg of catalyst, 1.5 kg of isophthalic acid, and 0.05 kg of curing accelerator.

[0063] The molecular weight of the methyl vinyl ether-maleic acid copolymer is 80,000, the catalyst is specifically monobutyl tin oxide, and the curing accelerator is specifically triphenylethylphosphine bromide.

[0064] Under nitrogen protection, neopentyl glycol, cyclohexanedimethanol, terephthalic acid, adipic acid, methyl vinyl ether-maleic acid copolymer, trimethylolpropane and a catalyst were mixed and reacted at 250°C for 4 hours, and water was distilled off during the reaction. The temperature was then lowered to 230°C and isophthalic acid was added to continue the reaction for 3 hours. The mixture was then vacuumed and polycondensed for 3 hours. The temperature was lowered to 210°C, and a curing accelerator was added. The reaction was continued for 0.6 hours, and the temperature was cooled to room temperature. The material was discharged to obtain a low-temperature curing polyester resin.

[0065] Preparatory Example 3

[0066] The preparation method of low temperature curing polyester resin comprises the following steps:

[0067] Weigh 3.7 kg of neopentyl glycol, 0.5 kg of cyclohexanedimethanol, 5 kg of terephthalic acid, 0.3 kg of adipic acid, 0.2 kg of trimethylolpropane, 0.05 kg of catalyst, 1.2 kg of isophthalic acid, and 0.02 kg of curing accelerator.

[0068] The activating agent is specifically monobutyltin oxide, and the curing accelerator is specifically triphenylethylphosphonium bromide.

[0069] Under nitrogen protection, neopentyl glycol, cyclohexanedimethanol, terephthalic acid, adipic acid, trimethylolpropane and a catalyst were mixed and reacted at 240°C for 3.5 hours, and water was distilled off during the reaction. The temperature was then lowered to 225°C and isophthalic acid was added to continue the reaction for 4 hours. The mixture was then vacuumed for condensation for 2 hours, the temperature was lowered to 200°C, a curing accelerator was added, the reaction was continued for 0.3 hours, the temperature was lowered to room temperature, and the material was discharged to obtain a low-temperature curing polyester resin.

[0070] Preparation Example 1

[0071] The preparation method of the modified degassing agent comprises the following steps:

[0072] Take polytetrafluoroethylene wax with an average molecular weight of 15000, perform low-temperature plasma treatment on the polytetrafluoroethylene wax, use HD cold plasma modification treatment instrument, glow discharge to generate plasma, nitrogen gas, treatment power of 200W, treatment time of 100s, and obtain pretreated polytetrafluoroethylene wax.

[0073] Weigh 100 g of pretreated polytetrafluoroethylene wax, 40 g of unsaturated polyoxyethylene ether, and 150 g of initiator solution.

[0074] The unsaturated polyoxyethylene ether is allyl alcohol polyoxyethylene ether, and the polymerization degree of allyl alcohol polyoxyethylene ether is 20; the initiator solution is composed of 98wt% of water and 2wt% of ammonium persulfate.

[0075] The pretreated polytetrafluoroethylene wax was stirred and dispersed in 2L of water, unsaturated polyoxyethylene ether was added and mixed evenly, and then the initiator solution was added dropwise, and the temperature was gradually raised to 80°C while the initiator solution was added dropwise. After the addition was completed, the reaction was continued for 3h. After the reaction was completed, it was filtered, the filter was collected and washed to obtain a modified degassing agent.

[0076] Preparation Example 2

[0077] The preparation method of the modified degassing agent comprises the following steps:

[0078] Take polytetrafluoroethylene wax with an average molecular weight of 15000, perform low-temperature plasma treatment on the polytetrafluoroethylene wax, use HD cold plasma modification treatment instrument, glow discharge to generate plasma, nitrogen gas, treatment power of 250W, treatment time of 60s, and obtain pretreated polytetrafluoroethylene wax.

[0079] Weigh 100 g of pretreated polytetrafluoroethylene wax, 50 g of unsaturated polyoxyethylene ether, and 200 g of initiator solution.

[0080] The unsaturated polyoxyethylene ether is prenol polyoxyethylene ether, and the polymerization degree of prenol polyoxyethylene ether is 10; the initiator solution is composed of 98wt% of water and 2wt% of ammonium persulfate.

[0081] The pretreated polytetrafluoroethylene wax was stirred and dispersed in 2L of water, unsaturated polyoxyethylene ether was added and mixed evenly, and then the initiator solution was added dropwise, and the temperature was gradually raised to 85°C while the initiator solution was added dropwise. After the addition was completed, the reaction was continued for 2h. After the reaction was completed, it was filtered, the filter was collected and washed to obtain a modified degasser.

[0082] Preparation Example 3

[0083] The preparation method of the modified degassing agent comprises the following steps:

[0084] Take polytetrafluoroethylene wax with an average molecular weight of 15000, perform low-temperature plasma treatment on the polytetrafluoroethylene wax, use HD cold plasma modification treatment instrument, glow discharge to generate plasma, nitrogen gas, treatment power of 200W, treatment time of 100s, and obtain pretreated polytetrafluoroethylene wax.

[0085] Weigh 100 g of pretreated polytetrafluoroethylene wax, 40 g of unsaturated polyoxyethylene ether, and 150 g of initiator solution.

[0086] The unsaturated polyoxyethylene ether is composed of 30g of allyl alcohol polyoxyethylene ether and 10g of isopentanol polyoxyethylene ether, the polymerization degree of allyl alcohol polyoxyethylene ether is 20, and the polymerization degree of isopentanol polyoxyethylene ether is 10; the initiator solution is composed of 98wt% of water and 2wt% of ammonium persulfate.

[0087] The pretreated polytetrafluoroethylene wax was stirred and dispersed in 2L of water, unsaturated polyoxyethylene ether was added and mixed evenly, and then the initiator solution was added dropwise, and the temperature was gradually raised to 80°C while the initiator solution was added dropwise. After the addition was completed, the reaction was continued for 3h. After the reaction was completed, it was filtered, the filter was collected and washed to obtain a modified degassing agent.

[0088] Preparation Example 4

[0089] The preparation method of the modified degassing agent comprises the following steps:

[0090] Take polytetrafluoroethylene wax with an average molecular weight of 15000, perform low-temperature plasma treatment on the polytetrafluoroethylene wax, use HD cold plasma modification treatment instrument, glow discharge to generate plasma, nitrogen gas, treatment power of 250W, treatment time of 60s, and obtain pretreated polytetrafluoroethylene wax.

[0091] Weigh 100 g of pretreated polytetrafluoroethylene wax, 50 g of unsaturated polyoxyethylene ether, and 200 g of initiator solution.

[0092] The unsaturated polyoxyethylene ether is composed of 35g of allyl alcohol polyoxyethylene ether and 15g of isopentanol polyoxyethylene ether, the polymerization degree of allyl alcohol polyoxyethylene ether is 30, and the polymerization degree of isopentanol polyoxyethylene ether is 15; the initiator solution is composed of 98wt% of water and 2wt% of ammonium persulfate.

[0093] The pretreated polytetrafluoroethylene wax was stirred and dispersed in 2L of water, unsaturated polyoxyethylene ether was added and mixed evenly, and then the initiator solution was added dropwise, and the temperature was gradually raised to 85°C while the initiator solution was added dropwise. After the addition was completed, the reaction was continued for 2h. After the reaction was completed, it was filtered, the filter was collected and washed to obtain a modified degasser.

[0094] Comparative Preparation Example 1

[0095] The preparation method of the modified degassing agent comprises the following steps:

[0096] Take polytetrafluoroethylene wax with an average molecular weight of 15000, perform low-temperature plasma treatment on the polytetrafluoroethylene wax, use HD cold plasma modification treatment instrument, glow discharge to generate plasma, nitrogen gas, treatment power of 200W, treatment time of 100s, and obtain pretreated polytetrafluoroethylene wax.

[0097] Weigh 100 g of pretreated polytetrafluoroethylene wax, 40 g of hydroxyethyl acrylate, and 150 g of initiator solution.

[0098] The initiator solution consists of 98 wt % of water and 2 wt % of ammonium persulfate.

[0099] The pretreated polytetrafluoroethylene wax was stirred and dispersed in 2L of water, hydroxyethyl acrylate was added and mixed evenly, and then the initiator solution was added dropwise, and the temperature was gradually raised to 80°C while the initiator solution was added dropwise. After the addition was completed, the reaction was continued for 3 hours. After the reaction was completed, it was filtered, the filter body was collected and washed to obtain a modified degassing agent.

[0100] Example 1

[0101] A method for preparing a calcium silicate board powder coating comprises the following steps:

[0102] Weigh 5.5kg of low-temperature curing polyester resin, 0.5kg of curing agent, 0.05kg of wetting agent, 0.05kg of leveling agent, 0.05kg of filler, 0.5kg of flame retardant, 0.06kg of modified degassing agent, and 3.29kg of pigments and fillers.

[0103] The low-temperature curing polyester resin is derived from Preparation Example 1, the curing agent is triglycidyl isocyanurate, the wetting agent is RK-8209 from Ruike Chemical, the leveling agent is BYK-333 from BYK Chemical, the filler is nano iron powder with a particle size of 50 to 100 nm, the flame retardant is aluminum hydroxide, the modified degassing agent is derived from Preparation Example 1, and the pigment and filler are titanium dioxide.

[0104] The low-temperature curing polyester resin, curing agent, wetting agent, leveling agent, filler, modified degassing agent and pigment filler are mixed, melted at 110° C. by a twin-screw extruder, extruded, cooled, crushed and sieved to obtain a calcium silicate board powder coating.

[0105] Example 2

[0106] A method for preparing a calcium silicate board powder coating comprises the following steps:

[0107] Weigh 7kg of low-temperature curing polyester resin, 0.8kg of curing agent, 0.15kg of wetting agent, 0.15kg of leveling agent, 0.15kg of filler, 1kg of flame retardant, 0.1kg of modified degassing agent, and 0.65kg of pigment and filler.

[0108] The low-temperature curing polyester resin is derived from Preparation Example 2, the curing agent is triglycidyl isocyanurate, the wetting agent is RK-8209 from Ruike Chemical, the leveling agent is BYK-333 from BYK Chemical, the filler is nano iron powder with a particle size of 50 to 100 nm, the flame retardant is aluminum hydroxide, the modified degassing agent is derived from Preparation Example 2, and the pigment and filler are titanium dioxide.

[0109] The low-temperature curing polyester resin, curing agent, wetting agent, leveling agent, filler, modified degassing agent and pigment filler are mixed, melted at 110° C. by a twin-screw extruder, extruded, cooled, crushed and sieved to obtain a calcium silicate board powder coating.

[0110] Example 3

[0111] A method for preparing a calcium silicate board powder coating comprises the following steps:

[0112] Weigh 6kg of low-temperature curing polyester resin, 0.6kg of curing agent, 0.1kg of wetting agent, 0.12kg of leveling agent, 0.12kg of filler, 0.8kg of flame retardant, 0.9kg of modified degassing agent, and 1.36kg of pigments and fillers.

[0113] The low-temperature curing polyester resin is derived from Preparation Example 1, the curing agent is triglycidyl isocyanurate, the wetting agent is RK-8209 from Ruike Chemical, the leveling agent is BYK-333 from BYK Chemical, the filler is nano iron powder with a particle size of 50 to 100 nm, the flame retardant is aluminum hydroxide, the modified degassing agent is derived from Preparation Example 1, and the pigment and filler are titanium dioxide.

[0114] The low-temperature curing polyester resin, curing agent, wetting agent, leveling agent, filler, modified degassing agent and pigment filler are mixed, melted at 110° C. by a twin-screw extruder, extruded, cooled, crushed and sieved to obtain a calcium silicate board powder coating.

[0115] Example 4

[0116] A method for preparing calcium silicate board powder coating.

[0117] The difference between this embodiment and embodiment 1 is that the modified degassing agent comes from preparation example 3.

[0118] Example 5

[0119] A method for preparing calcium silicate board powder coating.

[0120] The difference between this embodiment and embodiment 1 is that the modified degassing agent comes from preparation example 4.

[0121] Example 6

[0122] A method for preparing calcium silicate board powder coating.

[0123] The difference between this embodiment and embodiment 1 is that the low temperature curing polyester resin comes from preparation example 3.

[0124] Comparative Example 1

[0125] A method for preparing calcium silicate board powder coating.

[0126] The difference between this comparative example and Example 1 is that no modified degassing agent is added, and 0.06 kg of polytetrafluoroethylene wax with an average molecular weight of 15,000 is added instead.

[0127] Comparative Example 2

[0128] The difference between this comparative example and Example 1 is that the modified degassing agent comes from Comparative Preparation Example 1.

[0129] Performance Testing

[0130] The powder coatings prepared in Examples 1-6 and Comparative Examples 1-2 were coated. The specific process was as follows: the powder coatings were sprayed onto a calcium silicate board with a length and width of 20 cm using an electrostatic spray gun, and then cured at 160° C. for 15 minutes to form a coating, and the coating was completed after natural cooling.

[0131] Another calcium silicate board was coated with the powder coating of Example 1, the only difference being that the curing temperature was 200° C., as a control example.

[0132] Coating properties: Observe whether the coating has pits or orange peel, and touch the coating with your hand to feel whether it has obvious bumps and bumps.

[0133] Adhesion performance: Soak the coated calcium silicate board in boiling water for 2 hours, take it out, cool and dry it, and then adhere it to the coating surface with 3M tape. Then tear off the 3M tape and record the coating shedding situation by the cross-grid method.

[0134] Impact resistance: Place the coated calcium silicate board in a drop hammer impact tester with a weight of 1000g. The hammer falls naturally from a height of 50cm to impact the coating, and then observe whether cracks appear on the coating and the specific state of the cracks.

[0135] Resistance to moisture and heat: Place the coated calcium silicate board in a salt spray test box at 70°C and 80% humidity for 48 hours, then take it out and conduct an impact test.

[0136] The above test results are shown in Table 1 and Table 2.

[0137] Table 1

[0138] Coating properties Adhesion performance Example 1 No potholes, no orange peel, no bumpy touch No shedding Example 2 No potholes, no orange peel, no bumpy touch No shedding Example 3 No potholes, no orange peel, no bumpy touch No shedding Example 4 No potholes, no orange peel, no bumpy touch No shedding Example 5 No potholes, no orange peel, no bumpy touch No shedding Example 6 No potholes, no orange peel, no bumpy touch Shedding less than 5% Comparative Example 1 Potholes, orange peel, and noticeably uneven touch 50% to 60% shedding Comparative Example 2 Potholes, orange peel, and noticeably uneven touch 50% to 60% shedding Comparison Example Orange peel, bumpy touch 40% to 50% shedding

[0139] Table 2

[0140]

[0141]

[0142] As can be seen from Table 1, taking Examples 1-3 as an example, when the modified degassing agent is added and low-temperature curing is adopted, the coating has no orange peel or unevenness, and there is basically no falling off after boiling in water, which proves that the powder coating exhibits good adhesion and flatness on the calcium silicate board, overcomes the problem of poor performance of powder coating on calcium silicate board in the past, and has a high application prospect.

[0143] Combining Example 1 with the control example, it can be found that the final effect of the coating cured at a low temperature of 160°C is better than that of the coating cured at a high temperature of 200°C. Low-temperature curing can reduce the structural impact on the calcium silicate board itself, thereby ensuring the bonding strength between the powder coating and the calcium silicate board.

[0144] Combining Example 1 with Comparative Examples 1-2, it can be found that the modified degassing agent prepared by grafting unsaturated polyoxyethylene ether with polytetrafluoroethylene wax is superior to ordinary polytetrafluoroethylene wax and polytetrafluoroethylene wax grafted with hydroxyethyl acrylate in terms of adhesion and flatness.

[0145] It can be seen from Table 2 that, taking Examples 1-3 as an example, when a modified degassing agent is added and low-temperature curing is adopted, the powder coating exhibits good impact toughness and moisture and heat resistance on the calcium silicate board.

[0146] Combining Example 1 with Examples 4-5, it can be found that when the unsaturated polyoxyethylene ether is compounded with allyl alcohol polyoxyethylene ether and isopentanol polyoxyethylene ether, the moisture and heat resistance of the coating can be further improved, and the durability of the calcium silicate board powder coating can be improved.

[0147] Combining Example 1 with Example 6, it can be found that adding methyl vinyl ether-maleic acid copolymer during the preparation of low-temperature curing polyester resin can effectively enhance the toughness of the coating and provide better impact resistance.

[0148] This specific implementation manner is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the specific implementation manner as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A calcium silicate board powder coating, characterized in that: It is prepared from raw materials containing the following weight percentages: Low temperature curing polyester resin 55~70%; Curing agent 5~8%; Wetting agent 0.5~1.5%; Leveling agent 0.5~1.5%; Filler 0.5~1.5%; Flame retardant 5~10%; Modified degassing agent 0.6~1%; Pigment and filler residue; The modified degassing agent is prepared by grafting polytetrafluoroethylene wax with unsaturated polyoxyethylene ether; The low-temperature curing polyester resin is prepared from neopentyl glycol, cyclohexanedimethanol, terephthalic acid, isophthalic acid, adipic acid, methyl vinyl ether-maleic acid copolymer, trimethylolpropane, a catalyst and a curing accelerator; The filler is nano iron powder, and the particle size of the nano iron powder is 50-100 nm.

2. A calcium silicate board powder coating according to claim 1, characterized in that: The weight ratio of polytetrafluoroethylene wax to unsaturated polyoxyethylene ether used to prepare the modified degassing agent is 1:(0.4-0.5), and the unsaturated polyoxyethylene ether is selected from one or two of allyl alcohol polyoxyethylene ether and isopentanol polyoxyethylene ether.

3. A calcium silicate board powder coating according to claim 1, characterized in that: The unsaturated polyoxyethylene ether is a combination of allyl alcohol polyoxyethylene ether and isopentanol polyoxyethylene ether, and the weight ratio of the polytetrafluoroethylene wax, allyl alcohol polyoxyethylene ether and isopentanol polyoxyethylene ether is 1:(0.3-0.35):(0.1-0.15).

4. A calcium silicate board powder coating according to claim 3, characterized in that: The polymerization degree of the allyl alcohol polyoxyethylene ether is 20-30, and the polymerization degree of the isopentenol polyoxyethylene ether is 10-15.

5. The calcium silicate board powder coating according to claim 1, characterized in that: The raw materials for preparing the low temperature curing polyester resin are prepared according to the following weight ratio: 35-40 parts of neopentyl glycol; 5-10 parts of cyclohexanedimethanol; 50-55 parts of terephthalic acid; Isophthalic acid 12-15 parts; Adipic acid 3-7 parts; 2-4 parts of methyl vinyl ether-maleic acid copolymer; 2-4 parts of trimethylolpropane; Catalyst 0.5~1 part; Curing accelerator 0.2~0.5 parts 6. A method for preparing a calcium silicate board powder coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: The low-temperature curing polyester resin, curing agent, wetting agent, leveling agent, filler, flame retardant, modified degassing agent and pigment filler are mixed, melted, extruded, cooled, crushed and sieved to obtain the calcium silicate board powder coating.

7. The method for preparing a calcium silicate board powder coating according to claim 6, characterized in that: The preparation method of the modified degassing agent: The polytetrafluoroethylene wax is subjected to low temperature plasma treatment, with a treatment power of 200-250W and a treatment time of 60-100s to obtain pretreated polytetrafluoroethylene wax; The pretreated polytetrafluoroethylene wax is stirred and dispersed in water, unsaturated polyoxyethylene ether is added and mixed evenly, and then the initiator solution is added dropwise, and the temperature is gradually raised to 80-85°C while the initiator solution is added dropwise. After the addition is completed, the reaction is continued for 2-3 hours. After the reaction is completed, it is filtered, the filter body is collected and washed to obtain a modified degassing agent.

8. The method for preparing a calcium silicate board powder coating according to claim 6, characterized in that: The preparation method of the low temperature curing polyester resin: Under the protection of inert gas, neopentyl glycol, cyclohexanedimethanol, terephthalic acid, adipic acid, methyl vinyl ether-maleic acid copolymer, trimethylolpropane and a catalyst are mixed and reacted at 240-250°C for 3.5-4h, and water is distilled off during the reaction. Then the temperature is lowered to 225-230°C and isophthalic acid is added to continue the reaction for 3-4h. Then, vacuum is drawn to cause polycondensation for 2-3h, the temperature is lowered to 200-210°C, and a curing accelerator is added. The reaction is continued for 0.3-0.6h, the temperature is lowered, and the material is discharged to obtain a low-temperature curing polyester resin.

Citation Information

Patent Citations

  • Polyester resin for TGIC cured high-toughness powder coating and preparation method thereof

    CN103739830A

  • Method for manufacturing hydrophilic lubricating coating on surface of medical interventional catheter

    CN105983139A